2020
DOI: 10.1002/jbmr.4722
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mass, Density, Geometry, and Stress–Strain Index in Adults With Osteogenesis Imperfecta Type I and Their Associations With Physical Activity and Muscle Function Parameters

Abstract: Osteogenesis imperfecta (OI) is a clinically and genetically heterogeneous heritable connective tissue disorder mainly characterized by bone fragility and increased fracture risk. This study investigated bone parameters in adults with OI type I and their relationship with physical activity and muscle function parameters in comparison with controls. A total of 27 (15 women, 12 men) adults with OI type I and 27 healthy age‐ and sex‐matched controls, with mean age 45 years (range 18–72 years), were included. Peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…On a qualitative level, healthy samples showed a more homogeneous and coherent microarchitecture in the center compared to the OI samples, where we observed an inhomogeneous microarchitecture with both void and sclerotic parts. From a mechanical point of view, the microarchitecture in the center is important for an even load distribution and could be compared with trabecular bone architecture, which is known to be impaired in OI (42,43). Bevers et al recently reported similar observations of microarchitectural heterogeneity in trabecular bone in adults with OI using HR-pQCT (24), while Whittier et al quantified comparable void spaces within osteoporotic trabecular bone which led to poor bone quality reflected in decreased bone strength (25).…”
Section: Discussionmentioning
confidence: 99%
“…On a qualitative level, healthy samples showed a more homogeneous and coherent microarchitecture in the center compared to the OI samples, where we observed an inhomogeneous microarchitecture with both void and sclerotic parts. From a mechanical point of view, the microarchitecture in the center is important for an even load distribution and could be compared with trabecular bone architecture, which is known to be impaired in OI (42,43). Bevers et al recently reported similar observations of microarchitectural heterogeneity in trabecular bone in adults with OI using HR-pQCT (24), while Whittier et al quantified comparable void spaces within osteoporotic trabecular bone which led to poor bone quality reflected in decreased bone strength (25).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Hald et al reported that patients with OI type III have reduced values of aBMD and vBMD (assessed through HR-pQCT) compared to patients with less severe OI [30]. Several recent studies have reported how fragility fracture represents an important problem in patients with OI even during adulthood [25,31]. Particularly, in adults with OI, the risk of fragility fractures in addition to reduced bone strength also seems to be increased through altered biomechanical muscle-bone relationships [31].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have reported how fragility fracture represents an important problem in patients with OI even during adulthood [25,31]. Particularly, in adults with OI, the risk of fragility fractures in addition to reduced bone strength also seems to be increased through altered biomechanical muscle-bone relationships [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, further exploration found that 80% of OI patients experience inherent muscle weakness instead of reduced activity [10]. Meanwhile, adults with OI had lower lean mass, muscle size, and muscle density compared to healthy controls and presented with markedly impaired muscle function [11]. Therefore, besides bone fragility, OI may be correlated with low muscle mass and function.…”
Section: Introductionmentioning
confidence: 99%